2022
DOI: 10.1021/acsomega.2c03489
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and In Vitro Evaluation of Inclusion Complexes Formed between S-Allylcysteine and Cyclodextrins

Abstract: The present study prepared inclusion complexes of S -allylcysteine (SAC) and cyclodextrin (α, β, γ) by the freeze-drying (FD) method and verified the inclusion behavior of the solid dispersion. Also, the study investigated the effect of SAC/CD complex formation on liver tumor cells. Isothermal titration calorimetry (ITC) measurements confirmed the exothermic titration curve for SAC/αCD, suggesting a molar ratio of SAC/αCD = 1/1, but no exothermic/endothermic reaction was obtained for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The H-3 and H-6 protons of CD are located at the wide and narrow ring edges of CD, respectively . Tachikawa et al reported that 1 H– 1 H NOESY NMR spectroscopic results showed that S-allyl cysteine in garlic forms a cross-peak with H-6 of CD, revealing an inclusion mode . These results indicated that both βCD/DPU and HP-βCD/DPU are encapsulated by two molecules of CD from the narrow edge (H-6) to the wide edge (H-3), sandwiching the benzene ring of DPU.…”
Section: Resultsmentioning
confidence: 98%
“…The H-3 and H-6 protons of CD are located at the wide and narrow ring edges of CD, respectively . Tachikawa et al reported that 1 H– 1 H NOESY NMR spectroscopic results showed that S-allyl cysteine in garlic forms a cross-peak with H-6 of CD, revealing an inclusion mode . These results indicated that both βCD/DPU and HP-βCD/DPU are encapsulated by two molecules of CD from the narrow edge (H-6) to the wide edge (H-3), sandwiching the benzene ring of DPU.…”
Section: Resultsmentioning
confidence: 98%
“…The DSC curve of αCD shows three broad endothermic peaks at 79, 115, and 139 °C. These peaks are mainly attributed to the water loss from αCD crystals 35 , 36 . Also, a broad endothermic peak at 80–95 °C is recorded for the AzoC6/2αCD mixture as a consequence of water loss from αCD.…”
Section: Resultsmentioning
confidence: 99%
“…When the dextran solution was titrated with γ-cyclodextrin (Fig. 5a,5d), no signi cant enthalpy changes were observed, suggesting that the dextran did not interact strongly with the γ-cyclodextrin (Tachikawa, et al, 2022). This phenomenon was attributed to the fact that the dextran was too large to enter the cavity in the γ-cyclodextrin, and that the dextran is primarily hydrophilic whereas the cavity is hydrophobic (Saffarionpour & Diosady, 2023).…”
Section: Isothermal Titration Calorimetry Analysismentioning
confidence: 97%